Scheloribates (Scheloribates) latipes - Murvanidze, Maka; Cilbircioğlu, Cihan; Özdemir, Esengül; Inak, Emre (Zenodo, 2020)
Scheloribates (Scheloribates) latipes (C.L. Koch, 1844) Material – One specimen in Çiftlik Village, Tekçam Area, Taşköprü forest, N 41° 22′ 14.15′′, E 34° 22′ 36.05′′, alt. = 1272 m, 5 September 2018, tree trunk of P. nigra; three specimens in Karadedeoğlu Village, Taşköprü forest, N 41° 22′ 55.11′′, E 34° 24′ 03.56′′, alt. = 1204 m, 24 July 2018, tree trunk of P. nigra; one specimen in Çiftlik Village, Tekçam Area, Taşköprü forest, N 41° 15′ 19.75′′, E 34° 14′ 06.85′′, alt. = 1329 m, 15 May 2018, tree bark and debris of P. nigra . Previous record in Turkey – Konya (Dik et al. 1999). Global distribution – Semicosmopolitan. Ecology – All types of habitats.

Published as part of Murvanidze, Maka, Cilbircioğlu, Cihan, Özdemir, Esengül & Inak, Emre, 2020, Checklist of oribatid mites (Acari: Oribatida) of the Central Black Sea basin of Turkey with new records for the country, pp. 255-277 in Persian Journal of Acarology 9 (3) on page 267, DOI: 10.22073/pja.v9i3.61909, http://zenodo.org/record/5236444
Keywords: Arthropoda; Scheloribates; Arachnida; Scheloribates latipes; Animalia; Biodiversity; Scheloribatidae; Sarcoptiformes; Taxonomy; 15. Life on land